Pengaruh Konsentrasi Ragi Terhadap Karakteristik Tempe Jagung (Zea Mays L.) - Peri Andika, I Ketut; Duniaji, Agus Selamet; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This study aims to determine the effect of yeast concentration on the characteristics of corn tempeh and to determine the concentration of yeast to produce corn tempeh with the best characteristics. This study used a completely randomized design (CRD) with yeast concentration treatment consisting of 5 levels: 0.2%, 0.4%, 0.6%, 0.8%, 1%. The treatment was repeated 3 times to obtain 15 units of experiment. The data obtained were analyzed by analysed by variance and if the treatment had an effect on the observed variables, it was continued with Duncan's Multiple Range Test (DMRT). The concentration of yeast in the making of corn tempeh has a very significant effect on water content, ash content, protein content, fat content, carbohydrate content, aroma, color, taste, texture, and overall acceptance. The yeast concentration of 0.8% produced corn tempeh with the best characteristics, namely: water content 65.6%, ash content 0.05%, fat content 6.91%, protein content 9.57%, carbohydrate content 17.9%, color , taste, aroma, texture, overall acceptance was very like, the color is white, the texture is compact and the aroma and taste are typical of tempeh.